Seismic Retrofitting of Irregular Pre-80s Low-rise Conventional RC Building Structures - Han Ay Lie; Junaedi Utomo; Hsuan-Teh Hu; Lena Tri Lestari (Institute of Research and Community Outreach - Petra Christian University, 2021)
A resilience and seismic safety evaluation method of under-qualified concrete structures designed based on codes prior to the introduction of earthquake provisions is presented. A numerical method for evaluating and improving a structure’s performance and resilience through jacketing and Carbon Fiber Reinforced Polymers (CFRP) retrofitting was developed. The model analyzed the structure’s existing condition, inadequate elements were identified, and segments that required strengthening were determined. Retrofitting and external reinforcing techniques were applied, and their effectiveness evaluated. Elements identified as insufficient were subjected to a strengthening iteration process to ensure that all qualifications were fulfilled. It was proven that the numerical simulation was accurate, cost-effective and time-saving in evaluating deficient structures and the effectiveness of their strengthening methods. The numerical model and analysis in conjunction with the technology of jacketing and CFRP retrofitting provide a fast and straightforward solution for older structures in ameliorating their resilience and overall performance